Thermodynamic geometry of AdS black holes and black holes in a cavity - Peng Wang; Houwen Wu; Haitang Yang (European Physical Journal C: Particles and Fields, 2020)
Abstract The thermodynamic geometry has been proved to be quite useful in understanding the microscopic structure of black holes. We investigate the phase structure, thermodynamic geometry and critical behavior of a Reissner–Nordstrom-AdS black hole and a Reissner–Nordstrom black hole in a cavity, which can reach equilibrium in a canonical ensemble. Although the phase structure and critical behavior of both cases show striking resemblance, we find that there exist significant differences between the thermodynamic geometry of these two cases. Our results imply that there may be a connection between the black hole microstates and its boundary condition.